A novel mutation in RAB3GAP1 gene in Chinese patient causing the Warburg micro syndrome: A case report. Issue 2 (15th January 2021) - Zhou, Dan; Wang, Qiu; Liu, Hanmin
Abstract: Rationale: Warburg Micro syndrome is a rare, autosomal recessive disorder characterized by multiple organ abnormalities involving the ocular, nervous, and genital systems. This case report describes a novel mutation in the RAB3GAP1 gene associated with Warburg Micro syndrome. Patient concerns: A 6-month-old female infant with bilateral congenital cataracts and developmental delay was referred to our department for further assessment. She presented with facial dysmorphic features, including a prominent forehead, microphthalmia, wide nasal bridge, relatively narrow mouth, large anteverted ears, and micrognathia. Diagnoses: The patient was diagnosed with Warburg Micro syndrome based on clinical manifestations, as well as a novel homozygous mutation in RAB3GAP1: c.75–2A>C. Both parents were identified as heterozygotic carriers of this mutation. Interventions: Bilateral cataract extraction and anterior vitrectomy were performed at age 6 months, followed by physical rehabilitation. Convex lenses were used to protect the eyes postoperatively until intraocular lens implantation. Outcomes: Although the patient received physical rehabilitation, she suffered global developmental delay. Lessons: The c.75–2A>C mutation in RAB3GAP1 expands the spectrum of known mutations in this gene, and it may be associated with Warburg Micro syndrome. Genetic counselors may wish to take this finding into consideration, especially given the poor prognosis associated with the disease.